Investigation of Lubricant Oil influence on Ignition of Gasoline-like Fuels by a Detailed Reaction Mechanism. (August 2018) - Distaso, E.; Amirante, R.; Calò, G.; Palma, P. De; Tamburrano, P.; Reitz, R.D.
Abstract: A reaction mechanism, suitable for simulating the lubricant oil influence on the combustion process of gasoline-like fuels, is developed. The proposed work is motivated by evidences reported in the literature highlighting that lubricant oil droplets can be the most likely inducer of pre-ignition phenomena, as well as the fact that lubricant oil can represent the main source of very fine soot particles emitted from the engine. In other words, the mixture of fuel and lubricant oil, through complex physical and chemical reactions involving long hydrocarbons chains, can auto-ignite before the spark timing or, if not the case, can become one of the major candidates in the generation of soot precursors. Therefore, developing a reliable reaction mechanism able to simulate the oil-fuel mixture behavior and contribution in terms of pre-ignition and soot formation is fundamental for predicting the onset of knocking phenomena and particle size distributions of soot emissions. In this study, surrogate components reproducing the lubricant oil propensity to ignition were first identified. A detailed reaction mechanism was then developed and validated starting from existing mechanisms proposed for the single species. In particular, alkanes ranging from C16 to C18 were selected as oil surrogates. Zero-dimensional numerical simulations were conducted in order to validate the proposed mechanism versus literature experimental data aimed at reproducing the effect of commercial lubricants on ignition propensity of gasoline-like fuels. From this analysis it was possible to define a suitable composition of the surrogate mixture proposed to model lubricant oil effects.